2018
DOI: 10.1002/zaac.201800185
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Three‐dimensionally Ordered Macroporous TiO2 and TiO2/WO3 Composites and Their Photocatalytic Performance

Abstract: This work presents the characterization and preparation of three-dimensionally ordered macroporous TiO 2 and TiO 2 /WO 3 composite nanoparticles with enhanced visible-light-responsive properties for rhodamine B (Rh B) photodegradation. The 3DOM TiO 2 and TiO 2 /WO 3 composites were prepared through a dip-infiltrating sol-gel process using a polystyrene (PS) colloidal crystal template. The materials were characterized by SEM, TEM, XRD, BET, XPS and UV/Vis. The 3DOM TiO 2 /WO 3 composite structures ranged from w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
(43 reference statements)
1
9
0
Order By: Relevance
“…ATC‐P10 displayed highest photocatalytic activity of MB degradation with the removal rate of 99.4 % after 50 min. It is found from Figure b that the kinetic reaction of all the degraded MB solutions of the catalyst complies with the pseudo‐first‐order kinetics model . It could be found that the MB degradation rate constant of ATC‐P10 was 0.1085 min –1 , which almost 8.19 and 1.32 times higher than that of P25 and ZTOF‐1‐P10, respectively.…”
Section: Resultssupporting
confidence: 52%
“…ATC‐P10 displayed highest photocatalytic activity of MB degradation with the removal rate of 99.4 % after 50 min. It is found from Figure b that the kinetic reaction of all the degraded MB solutions of the catalyst complies with the pseudo‐first‐order kinetics model . It could be found that the MB degradation rate constant of ATC‐P10 was 0.1085 min –1 , which almost 8.19 and 1.32 times higher than that of P25 and ZTOF‐1‐P10, respectively.…”
Section: Resultssupporting
confidence: 52%
“…To further accelerate the photo‐excited charge separation, TiO 2 /WO 3 IOPCs heterojunction electrode was designed and used in the PEC decomposition of RhB under the simulated solar light. [ 46 ] Recently, as shown in Figure 9, the BiVO 4 /WO 3 IOPCs heterojunction photoelectrodes with strong visible‐light response were fabricated based on the well‐matched band edge positions. [ 47 ] They further exhibited better removal ability towards RhB with a degradation rate constant of 0.286 h –1 and a photocurrent density of 5.04 mA·cm –2 at 1.2 V vs. Ag/AgCl under AM 1.5 illumination, which was larger than those of other BiVO 4 modified TiO 2 semiconductor photoelectrodes (BiVO 4 /TiO 2 heterojunction: rate constant of 0.242 h –1 , photocurrent density of 3.2 μA·cm –2 ; BiVO 4 /bi‐phase TiO 2 hierarchical nanofibers: photocurrent density of 4.8 μA·cm –2 ).…”
Section: Application Of Wo3 Iopcsmentioning
confidence: 99%
“…In recent years, more and more attention has been paid to TiO 2 due to its excellent photocatalytic performance, chemical stability, low cost and others, and it has a broad application prospect in the photocatalytic oxidation of environmental pollutants . However, the bandgap of TiO 2 photocatalyst is relatively wide (3.2 eV), which can only be excited by short‐wavelength ultraviolet light, and its utilization rate of solar energy is very low.…”
Section: Introductionmentioning
confidence: 99%